Influence of Environment Conditions on the Chemical Composition and Antioxidant Activity of Larrea divaricata Aqueous Extract - Alonso, Maria del Rosario (2012)
Natural antioxidants have gained considerable interest for their role in the prevention of autooxidation of fats and oils. Larrea divaricata Cav. is a South American plant widely distributed in Argentina with reported antioxidant, antitumoral and antimicrobial activities. The aqueous extract of the plant exerts antioxidant activity preventing the deleterious effect of temperature and oxygen on the antioxidant activity of vitamin C (Vit C). The aim of this work was: to assess the stability of the aqueous extract of L. divaricata (AE) under different environment conditions, such as different temperatures and air oxygen contents. The stability parameters evaluated included the percentage of majority compounds (flavonoid expressed as quercitrin (F) and nordihydroguaiaretic acid (NDGA)) and the antioxidant activity of the extract (AC). Results indicated that both compounds were affected by temperature and air oxygen, with F being more stable to high temperatures than NDGA, finding a decrease of 56% for F and a decrease ≥ 66% for NDGA. Nevertheless, NDGA was more sensitive to air oxygen, as an early decrease of 62% and a maximum decrease of 100% were found. The AC of AE decreased with high temperatures; however, air oxygen seemed to have a more important effect, for a decrease of about 42% was observed after 7 days of incubation. Even though, the environment conditions could affect the chemical composition of the whole extract, it was observed that not all the compounds were equally affected by temperature and air oxygen. Reaching a balance between these two parameters could allow a modulation of the antioxidant activity of this extract.